Pengaruh Prediksi Kebangkrutan, Debt Default, Kualitas Audit Dan Kondisi Keuangan Terhadap Opini Going Concern Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa EfekIndonesia Periode 2011-2014 - Juwita, Desi Ratna; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2016)
Going concern audit opinion issued an opinion of the auditor to determine whether the company can maintain its viability in the future to come. This study aimed to test predictions about the effect of bankruptcy, debt default, audit quality, and financial condition of the going concern audit opinion. The sample used in this study were obtained by purposive sampling, which accumulated as many as 40 companies. Data analysis tools in this research is to use regression logistics. Logistic regression analysis using multivariate testing, such as testing the overall model fit test, the coefficient of determination, the feasibility of regression models, and hypothesis testing. The variable in this study is the prediction of bankruptcy, debt default, audit quality, and financial condition. The results showed that the prediction of bankruptcy, debt default and financial conditions affect the going concern audit opinion, while the quality of audit does not affect the going concern audit opinion.